Medical Image Compression Using Hybrid Compression Techniques - Ashraf Dhannon Hasan, Abbas Salim Kadhim, Mustafa A. Ali (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Medical images are crucial in today’s healthcare system for diagnosis, but managing the large volume of images generated by different imaging methods is a challenge for Hospital Management Systems (HMS). Image compression, the process of reducing redundancies in image data, helps to store and transmit images efficiently by reducing the file size. This not only saves storage space, but also makes it easier to send images over limited bandwidth channels. Image compression is therefore an important factor in managing medical images for storage and transmission. In this research many loss and lossless compression methods are tested. Then hybrid combinations of these method are used to design an accurate hybrid compression system suitable for medical image. The best compression result is acquired when the Discrete Cosine Transform (DCT) and Discrete Wavelet Transform (DWT) are combined, their hybrid compression ratio is 9.348.